Free trade or fair trade? NAFTA and agricultural labor. - YOUNG, Linda Wilcox (1995)
Expresses concern on the impact of NAFTA on agricultural workers on both sides of the US/Mexico border. Additionally, the dislocation of workers and social disruption to communities resulting from changing crop mixes, production technologies, and land tenure patterns cannot be measured in aggregate employment statistics.